A pathway to 25% reduction in greenhouse gas emission by 2030 using GIS-Based multi-criteria decision making for renewables, date palm (phoenix dactylifera), and carbon credits: a case for Qatar - Bilal, Hazrat; Okonkwo, Eric C.; Al-Ansari, Tareq (Frontiers in Energy Research, 2024)
Qatar is making concerted efforts at the national level to decrease anthropogenic greenhouse gas emissions. The country has set its National Determined Contribution (NDC) in line with the Paris Agreement to reduce its overall emissions by 25% by the year 2030. This study identifies several pathways, which Qatar can explore to achieve its set goals. It explores Qatar's potential for RE generation (solar and wind), carbon offset through planting trees, and the purchase of carbon offset credits. The study starts by investigating the available wind and solar energy potential in the country, by considering physical and legal restrictions, which limit the available land to be utilized for RE generation. Multi-criteria Decision is carried out utilizing the Analytical Hierarchy Process (AHP) for variable percentage estimation in ArcMap GIS software. Next, a review based on Qatar's climate is performed to identify suitable tree species that would promote atmospheric CO2 sequestration in the country. Finally, the cost implication of offsetting emissions using verified carbon credits is considered and compared with other options. Results indicated that while a considerable area is available for both wind (37%) and solar (54%) energy generation, only 6.2% and 13.8% of Qatar are highly suitable for wind and solar energy installations, respectively. Also, while Qatar has the potential to meet 20% of its energy demand by 2030 from renewable sources by using solar PV and wind, this will only account for a 14.28% reduction in overall emissions.Additionally, planting date palm trees (Phoenix dactylifera) would significantly benefit the nation in the area of carbon sequestration and revenue generation as compared to purchasing carbon offset credits.